Stimulus effects of propylene glycol and vegetable glycerin in electronic cigarette liquids. (1st January 2019) - Harvanko, Arit; Kryscio, Richard; Martin, Catherine; Kelly, Thomas
Highlights: Vegetable glycerin is associated with visible electronic cigarette exhalant (i.e., cloud). Propylene glycol and vegetable glycerin mixtures enhance reported smoking sensations. Neither propylene glycol or vegetable glycerin influenced measures of abuse liability. Abstract: Background: Little is known about the behavioral effects of non-nicotine ingredients in electronic cigarette liquids. Propylene glycol (PG) and vegetable glycerin (VG) are the most common humectants used in electronic cigarette liquids. These ingredients may influence stimulus effects (e.g., visibility of exhalant, taste, or smell), which have played a role in the abuse liability of conventional cigarettes. In the current study, the stimulus effects of aerosol from liquids varying only in PG and VG content were assessed. Methods: Sixteen electronic cigarette users completed five sessions (one practice and four testing sessions). Following one hour of nicotine deprivation, two sampling puffs from liquid formulations containing 100/0, 75/25, 50/50, 25/75, and 0/100% PG/VG concentrations were administered in random order during five assessments, each separated by 20 min. Measures included self-reported stimulus effects and breakpoint on a multiple-choice procedure with options consisting of sampled puffs or varying amounts of money. Results: VG content was associated with greater reports of visibility of the exhalant (i.e., "cloud"). Liquids with only PG or VG engendered lower reports of inhalation sensations (e.g., throat hit) and greater reductions of systolic blood pressure compared to mixtures of PG and VG. There was no effect of liquid formulation on the multiple-choice procedure, but puffs were rarely chosen over even the smallest monetary option (0.05), suggesting minimal reinforcing efficacy. Conclusions: Liquids containing greater concentrations of VG are more capable of producing visible exhalant and mixtures of PG and VG engender greater airway sensory effects than either ingredient alone.